An Impact Vibration Experimental Research on the Pretension Rectangular Membrane Structure. (4th October 2015) - Guo, Jianjun; Zheng, Zhoulian; Wu, Song
Abstract : The pretension of the membrane is applied with biaxial tension bracket; the digital dynamometer is used for measuring the change of the tension; the concentrated impact load is applied on the surface of rectangular membrane; the displacement change of each feature point on the membrane surface is measured by noncontact laser displacement sensor. Through this experiment, the vibration displacement-time curve of the rectangular membrane under the fixed boundary condition is obtained. Further, the vibration frequency is given, according to the power spectral density function. The results of the experimental research are used to verify and correct theoretical formula and make the foundation for further theoretical research.